Speaking with Distance: Exploring the Effectiveness of Remote Practice - Tauchid, Ahmad; Seftika; Zumrudiana, Ainu; Suwandi, Edi (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The rising prominence of remote speaking practice in education and professional development underscores its critical significance. Enabled by advancing technology, remote platforms offer unprecedented convenience and accessibility for individuals to refine speaking skills. Research explores the efficacy of remote speaking practice, drawing on previous studies that have examined technology-mediated communication for language learning and public speaking training. Building on this foundation, this study investigates students' perceptions of remote speaking tasks' impact on pronunciation, speaking skills, and confidence. Through a qualitative approach involving open-ended surveys distributed to 19 English students at one of the Islamic private universities in Indonesia, attitudes and motivations shaping students' perspectives are explored. Analysis using NVivo 12 highlights the pivotal role of remote speaking tasks in improving pronunciation skills and fostering English speaking proficiency. Moreover, students' recognition of confidence as integral to successful language learning underscores the importance of supportive learning environments. The findings underscore the necessity of integrating remote speaking tasks into language curricula to enhance pronunciation and speaking proficiency effectively while emphasizing the pivotal role of confidence in facilitating language acquisition. These insights hold significant implications for language education, advocating for the incorporation of remote speaking practice to empower learners in developing fluency and proficiency in virtual environments.